2023
DOI: 10.1039/d3sc00912b
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox radical/polar crossover enables C–H gem-difunctionalization of 1,3-benzodioxoles for the synthesis of monofluorocyclohexenes

Abstract: A photocatalytic C-H gem-difunctionalization of 1,3-benzodioxoles with two different alkenes for the synthesis of highly functionalized monofluorocyclohexenes is desribed. Using 4CzIPN as the photocatalyst, the direct single electron oxidation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Based on the above results and also considering the related literature reports, 12 a ,15 c ,16,19 a plausible reaction mechanism is proposed for the present transformations (Scheme 5). First, a phosphinoyl radical ( B ) is produced via proton-coupled electron transfer (PCET) oxidation in the presence of K 2 CO 3 and photoexcited catalysts (PCET-a).…”
Section: Resultssupporting
confidence: 70%
“…Based on the above results and also considering the related literature reports, 12 a ,15 c ,16,19 a plausible reaction mechanism is proposed for the present transformations (Scheme 5). First, a phosphinoyl radical ( B ) is produced via proton-coupled electron transfer (PCET) oxidation in the presence of K 2 CO 3 and photoexcited catalysts (PCET-a).…”
Section: Resultssupporting
confidence: 70%
“…Zhou and co-workers described a one-pot, two-step, three-component defluorinative annulation of trifluoromethyl alkenes, alkenes, and sodium sulfinates under photocatalysis . Very recently, the dual C–F bond functionalization of trifluoromethyl alkenes for accessing a monofluorocyclohexene framework was enabled through a stepwise photoredox radical/polar crossover procedure . Inspired by these elegant works and in continuation of our interest in defluorinative reactions, we herein presented a formal hydrophosphorylation reaction of β-CF 3 -substituted enones by combining hydrodefluorination and defluorophosphorylation in one pot.…”
mentioning
confidence: 97%
“…On the basis of these control experiments and previous reports, we proposed a plausible reaction mechanism (Scheme ). Initially, the carbonyl-containing trifluoromethyl alkenes react with reductive PhSiH 3 to realize hydrodefluorination through an S N 2′-type nucleophilic process and a simultaneous carbonyl reduction, leading to gem -difluorinated alkene B (pathway a). Subsequently, phosphoryl anion D selectively adds to the highly electrophilic α-position in gem -difluoroalkenes, followed by β-fluorine elimination to deliver the desired product 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In path B, radical intermediate III is reduced to zwitterion IV first. Then the product P2 is obtained via the elimination of pyridine . The results of density functional theory (DFT) calculations indicated that the free energy of zwitterion IV is 7.41 kcal/mol lower than that of diradical V (see the Supporting Information).…”
mentioning
confidence: 99%